2007
DOI: 10.1093/cercor/bhl153
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Activation for Autobiographical Memories over the Entire Lifetime in Healthy Aged Subjects: An fMRI Study

Abstract: We used functional magnetic resonance imaging to determine the cerebral structures required during the recollection of episodic autobiographical memories according to 5 time periods covering the whole lifespan to test the 2 concurring models of memory consolidation, which propose either a temporary (standard model) or a permanent (multiple-trace model) role of the hippocampus in episodic memory retrieval. The experimental paradigm was specially designed to engage subjects (67.17 +/- 5.22 years old) in the retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
161
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 110 publications
26
161
0
3
Order By: Relevance
“…SCM predicts greater hippocampal activity for recent than remote AMs (i.e., a remoteness effect), whereas MTT predicts that if both types of AMs are equally detailed and vivid, they should elicit similar hippocampal activity (i.e., no remoteness effect). Although a few functional neuroimaging studies found the remoteness effect predicted by SCM (Niki & Luo, 2002;Piefke, et al, 2003) most of the studies comparing remote and recent AMs did not, supporting MTT Conway, et al, 1999;Gilboa, et al, 2004;Maguire & Frith, 2003b;Maguire, et al, 2001;Piolino et al, 2004;Rekkas & Constable, 2005;Ryan, et al, 2001;Viard et al, 2007) and consistent with emerging evidence in the patient literature, which suggests that MTL damage can impact remote AMs greater than was previously found (Steinvorth, et al, 2005). However, neuroimaging evidence cannot irrefutably determine the necessity of the hippocampus in the retrieval of remote AMs.…”
Section: Remote Autobiographical Memoriessupporting
confidence: 54%
See 1 more Smart Citation
“…SCM predicts greater hippocampal activity for recent than remote AMs (i.e., a remoteness effect), whereas MTT predicts that if both types of AMs are equally detailed and vivid, they should elicit similar hippocampal activity (i.e., no remoteness effect). Although a few functional neuroimaging studies found the remoteness effect predicted by SCM (Niki & Luo, 2002;Piefke, et al, 2003) most of the studies comparing remote and recent AMs did not, supporting MTT Conway, et al, 1999;Gilboa, et al, 2004;Maguire & Frith, 2003b;Maguire, et al, 2001;Piolino et al, 2004;Rekkas & Constable, 2005;Ryan, et al, 2001;Viard et al, 2007) and consistent with emerging evidence in the patient literature, which suggests that MTL damage can impact remote AMs greater than was previously found (Steinvorth, et al, 2005). However, neuroimaging evidence cannot irrefutably determine the necessity of the hippocampus in the retrieval of remote AMs.…”
Section: Remote Autobiographical Memoriessupporting
confidence: 54%
“…Also, there is evidence of hemispheric asymmetries in the remoteness effect (Maguire & Frith, 2003b;Viard, et al, 2007), and aging is known to reduce hemispheric asymmetries in brain activity (Cabeza, 2002). In fact, fMRI studies have found activity in the left hippocampus in young adults, whereas, bilateral activity has been found in older adults for some remote periods (Maguire & Frith, 2003a;Viard, et al, 2007), but the effects of remoteness and age have not been disentangled.…”
Section: Age Of the Participants Investigating The Neural Correlatesmentioning
confidence: 99%
“…Some authors consider the hippocampus essential for consolidation and for retrieval of recent but not remote declarative memories (Squire Kirwan et al 2008). Others propose that the hippocampus remains vital in recollection (Nadel and Moscovitch 1997;Rosenbaum et al 2008), provided the remote memories are reexperienced vividly Viard et al 2007;Piolino et al 2008). Since AM recollection tends to lose its vividness over time Piolino et al 2008), we contend that the attenuation in hippocampal activity might be attributed to reduced vividness in recollection.…”
Section: The Passage Of Time Increases Acceptance Of Wrong Detailsmentioning
confidence: 74%
“…These regions were selected based on their reported involvement in consolidation and retrieval of episodic memories Cabeza and Jacques 2007;Viard et al 2007). Data from the VQ test at both Recent and Remote interval scans were extracted for the above ROIs, using GLM 1 (''general'' model) and GLM 3 (''confidence'' model).…”
mentioning
confidence: 99%
“…Andere Bildgebungsstudien berichten flache oder keine Zeitgradienten der Hippocampusaktivität im Zusammenhang mit dem Abruf autobiographischer Episoden und unterstützten insofern eher die MTT (z.^B. Ryan et al 2001;Viard et al 2007;Cabeza und St. Jacques 2007). Abbildung 4 zeigt die differentiellen Aktivierungen des Hippocampus während des Abrufs rezenter emotionaler autobiographischer Episoden (relativ zu emotionalen Erinnerungen an Kindheitsepisoden), die Piefke et al (2003) berichteten.…”
Section: Der Präfrontale Kortexunclassified